lm+n-3l+m^2n^2+4mn+4=0 求(4m-n)(m-2n)-(n-m)(-m-n)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 02:56:55
lm+n-3l+m^2n^2+4mn+4=0求(4m-n)(m-2n)-(n-m)(-m-n)lm+n-3l+m^2n^2+4mn+4=0求(4m-n)(m-2n)-(n-m)(-m-n)lm+n-3
lm+n-3l+m^2n^2+4mn+4=0 求(4m-n)(m-2n)-(n-m)(-m-n)
lm+n-3l+m^2n^2+4mn+4=0 求(4m-n)(m-2n)-(n-m)(-m-n)
lm+n-3l+m^2n^2+4mn+4=0 求(4m-n)(m-2n)-(n-m)(-m-n)
lm+n-3l+m^2n^2+4mn+4=0
lm+n-3l+(mn+2)²=0
则:
m+n-3=0
mn+2=0
解得:
m+n=3
mn=-2
m²+n²=(m+n)²-2mn=9+4=13
(4m-n)(m-2n)-(n-m)(-m-n)
=4m²-9mn+2n²+n²-m²
=3m²+3n²+18
=3(m²+n²)+18
=39+18
=57
lm+n-3l+m^2n^2+4mn+4=0 求(4m-n)(m-2n)-(n-m)(-m-n)
若lm-3l+(n+2)平方=0,则m+2n=
若lm-3l+[n+9]2=0 那么[m+3]-[n-9]=
若lm-3l+[n+9]2=0 那么[m+3]-[n-9]=
m-n=7 mn=-5求(3m+5n+4mn)-(2n-4n+6mn)
3(m^2n+mn)-4(mn-2m^2n)+mn.要有过程
已知m-n=2,mn=1,求多项式(-2mn+2mn+3n)-(3mn+2n-2m)-(m+4n+mn)的值
已知m-n=2,mn=1,求多项式(-2mn+2mn+3n)-(3mn+2n-2m)-(m+4n+mn)的值
已知m-n=4,mn=2,求多项式(-2mn+2m+3n)-(3mn+2n-2n)-(m+4n+mn)的值
已 知m-n=4,mn=-1,求:(-2mn+2m+3n)-(3mn+2n-2n)-(m+4n+mn)的值
已知m-n=4,mn=2,求多项式(-2mn+2m+3n)-(3mn+2n-2m)-(m+4n+mn)的值.
已知m-n=4,mn=-1,求(-2mn+2m+3n)-(3mn+2n-2m)-(m+4n+mn)的值.
若m-n=4,mn=-1,求(-2mn+2m+3n)-(3mn+2n-2m)-(m+4n+mn)
若m-n=4,mn=-1求(9-2mn+2m+3n)-(3mn+2n-2m)-(m+4n+mn)
已知m-n=4,mn=-1,求(-2mn+2m+3n)-(3mn+2n-2m)-(m+4n+mn)的值
已知m-n=3,mn=-3,求(-m-4n-mn)-(2mn-2m-3n)-(3mn+2n-2m)的值
已知m-n=2,mn=1,求多项式(2mn+2m+3n)-(3mn+2n-2m)-(m+4n+mn)的值
已知|m-n-2|与(mn-1)^互为相反数,求(-2mn+2m+3n)-(3mn+2n-2m)-(m+4n+mn)的值